PERLINDUNGAN HUKUM TERHADAP HAK-HAK TERDAKWA DALAM PENYELESAIAN PERKARA PIDANA DI GORONTALO - Nopiana Mozin (PT. Jurnal Center Indonesia Publisher, 2024)
Based on research results witness or victim protection is regulated in Law no. 13 of 2006 and to find out how the legal protection of the rights of the defendant in criminal cases in Gorontalo the violation of the defendant was carried out by the investigator both from the beginning of the process until the end of the process. The human rights law must be fulfilled and there are several violations committed by the investigator both intentionally or unintentionally. The defendant's human rights are listed in Law No. 8 of 1981 concerning criminal procedural law in article 98 paragraph 1 explains